Participatory Generation of Market-Driven Technology under Agriculture 5.0: Concepts, Tools, Practices, Prospects and Challenges - Jardinero, Benedict (International Rice Research Institute, 2025)
"This lecture presentation was developed and delivered under Session 4 of the 2025 Training on Transformational Agricultural Innovation Systems for the New Future (TrAInS), focusing on participatory, market-driven technology development. The session introduced two key CGIAR-endorsed approaches: Human-Centered Design (HCD) and Innovation Packages and Scaling Readiness (IPSR), offering training participants the practical tools and frameworks to design innovations that are aligned with user needs, local contexts, and scalable impact pathways. With a strong emphasis on inclusive stakeholder engagement and interdisciplinary collaboration, the session aimed to build awareness and capacities for demand-driven agricultural research and development. It provided both conceptual grounding and real-world examples to support 32 participants from academic and research institutions across the ASEAN region in applying these approaches to their institutional and field contexts. TrAInS was organized by the Southeast Asian Regional Center for Graduate Study and Research in Agriculture (SEARCA). It was conducted at SEARCA Headquarters in Los Baños, Laguna, Philippines, from 16 to 20 June 2025."